Interaction of supercavitating strikers with underwater obstacles - Ishchenko, Aleksandr N.; Burkin, Viktor V.; Diachkovskii, Alexei S.; Rogaev, Konstantin S.; Sammel, A. Yu; Sidorov, A. D.; Stepanov, E. Yu; Chupashev, Andrey V. (Journal of engineering physics and thermophysics)
The interaction of supercavitating strikers with obstacles placed in water was investigated in a wide range of intersection angles. Several options of the interaction of strikers with obstacles are considered, including through puncturing, destruction of the striker, and ricochet. Estimation was made of the magnitude of the decrease in the speed of strikers in the cases of through puncturing and ricochet.